Material properties of ultra-high molecular weight polyethylene: Comparison of tension, compression, nanomechanics and microstructure across clinical formulations. (July 2018) - Malito, Louis G.; Arevalo, Sofia; Kozak, Adam; Spiegelberg, Stephen; Bellare, Anuj; Pruitt, Lisa
Abstract: This is the first study to simultaneously measure material properties in tension, compression, nanoindentation as well as microstructure (crystallinity and lamellar level properties) across a wide variety of clinically relevant ultra-high molecular weight polyethylene (UHMWPE) formulations. Methodologies for the measurement of UHMWPE mechanical properties—namely elastic modulus, yield stress, yield strain, ultimate strength, energetic toughness, Poisson's ratio, hardness and constitutive variables—are evaluated. Engineering stress-strain behavior is compared to true stress-strain behavior for UHMWPE across a range of cross-linking and antioxidant chemistry. The tensile mechanical properties and constitutive behavior of UHMWPE are affected by resin type, antioxidant source and degree of cross-linking. Poisson's ratio is shown to be affected by resin type, antioxidant addition, and cross-linking dosage. Relationships between bulk mechanical properties from different measurement methodologies as well as microstructure are analyzed across all material formulations using Spearman rank correlation coefficients. Modulus and yield strength correlate in both tension and compression. Similarly, tensile and compressive properties including modulus and yield strength correlate strongly with crystallinity ( X c ) and lamellar thickness ( D ). This work has broad application and provides a basis for interpreting the mechanical behavior of UHMWPE used in orthopedic implants.